1987
DOI: 10.1021/ic00260a028
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the stabilities of monomeric metal ion complexes formed with adenosine 5'-triphosphate (ATP) and pyrimidine-nucleoside 5'-triphosphate (CTP, UTP, TTP) and evaluation of the isomeric equilibria in the complexes of ATP and CTP

Abstract: 070ChemInform Abstract The stability constants for the divalent metals Mg, Ca, Mn, Co, Ni, Cu, Zn, and Cd are determined by potentiometric pH titrations at 25 rc C. The results show that the stability of most of the M(ATP)2-complexes is significantly larger than that of the corresponding complexes formed with the pyrimidine-nucleoside 5'-triphosphates (PNTP). This increased stability is attributed to the formationof outer-sphere macrochelates. Inner-and outer-sphere forms of M(ATP)2-occur for Mn, Co, Ni, Zn, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
160
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 135 publications
(169 citation statements)
references
References 3 publications
5
160
0
Order By: Relevance
“…2,3,18,19 As expected, any kind of chelation 28 must be reflected in an enhanced complex stability and this also holds for the mentioned cases. 16,17,26 Of course, macrochelates as indicated in equilibrium (1) will hardly form to 100%. Therefore, (1), and is given by equation (8):…”
Section: Proof Of Macrochelate Formation In the M(np) 0/-/2-and M(dnpmentioning
confidence: 99%
See 3 more Smart Citations
“…2,3,18,19 As expected, any kind of chelation 28 must be reflected in an enhanced complex stability and this also holds for the mentioned cases. 16,17,26 Of course, macrochelates as indicated in equilibrium (1) will hardly form to 100%. Therefore, (1), and is given by equation (8):…”
Section: Proof Of Macrochelate Formation In the M(np) 0/-/2-and M(dnpmentioning
confidence: 99%
“…The results obtained now for equilibria (4a), (5a) and (6a), where NP = dAMP 2-, dADP 3-or dATP 4-, are listed in Table 1 together with the corresponding equilibrium constants for the M 2+ /AMP 2-, ADP 3-and ATP 4-systems taken from earlier work, [16][17][18] as well as some other related data. [18][19][20][21] The results of (i) and (ii) are almost identical and hence, the average of the two calculation procedures is expected to be a reliable estimate: log K Ni(dGMP) Ni = 3.68 ± 0.09 is listed in Table 1 (entry 1b).…”
Section: Definition Of the Equilibrium Constants And Corresponding Rementioning
confidence: 99%
See 2 more Smart Citations
“…In a comprehensive structural investigation of the MnGMP complex using ESEEM and electron spinecho electron-nuclear double resonance (ESE-ENDOR), we found the Mn 2ϩ ion to take a single inner-sphere ligand (N7) from the nucleotide, implying a pentahydrate structure (Hoogstraten et al+, 2002)+ This same configuration was found for MnGMP in the crystal state (de Meester et al+, 1974)+ MnGMP was therefore used as a first test case for the water-counting methodology+ Figure 3 shows experimental three-pulse ESEEM data for Mn 2ϩ ligated to GMP, treated to isolate contributions from inner-sphere D 2 O, at three different magnetic fields corresponding to maxima in the field-swept ESE-EPR spectrum (Fig+ 3D)+ Expected curves for the cases of one to six inner-sphere waters of hydration, derived from experimental data for the Mn(H 2 O) 6 complex, are shown for comparison+ At each field, the data are visually consistent with a pentahydrate structure, judged primarily by the initial depth of 2 H modulation+ Quantitative analysis of the data (Materials and Methods) yields a hydration level of 5+2 6 0+1+ These results are fully consistent with our earlier analysis indicating a Determining hydration level of bound metal ions 253 single nucleotide-derived ligand to the octahedral Mn 2ϩ (Hoogstraten et al+, 2002)+ Because of the biological importance of ATP and the common use of Mn 2ϩ complexes of adenine nucleotides as spectroscopic probes of enzyme active sites, the complex of Mn 2ϩ with ATP has been thoroughly investigated by a number of methods (Aoki, 1996;Sigel & Song, 1996; and references therein)+ Sigel and coworkers determined that ligation of Mn(II) to the triphosphate moiety of MnATP is extended into a macrochelate structure by additional ligation to the heterocyclic nitrogen N7 to an extent of 17% 6 10%, but they could not distinguish between inner-and outer-sphere ligation to N7 (Sigel 1987;Sigel et al+, 1987)+ Using ultraviolet probes of the aromatic ring, Mariam and Martin (1979) estimated an occurrence of 10% for the N7 innersphere complex but stated that this analysis was not highly quantitative+ In addition, even for this wellcharacterized complex, the number of inner-sphere ligands derived from ATP phosphates, and therefore the hydration level of the Mn 2ϩ ion, has not been determined with precision+ ESEEM of solvent-derived 2 H provides direct structural data that bear on these questions+ For a sample containing equimolar Mn 2ϩ and ATP, we find (Fig+ 4) a hydration level of 3+8 6 0+1, from which we conclude that Mn 2ϩ in 1:1 complex with ATP exists on average as a tetrahydrate+ Using 14 N ESEEM, we found no evidence for direct ligation to nitrogen in a 1:1 MnATP complex (C+G+ Hoogstraten, C+V+ Grant, and R+D+ Britt, in prep+), implying that all non-aqua ligands derive from phosphate groups+ Our data do not exclude a fraction of the complex existing as an outer-sphere macrochelate to N7, but any innersphere macrochelate is present at a level too low to be detectable using ESEEM+ Our results lead to the model shown in Figure 5 for the complex structure+ We note that the illustrated biphosphate (tetrahydrate) coordination at Mn 2ϩ is an ensemble average+ For example, equal quantities of monophosphate-and triphosphate-coordinated Mn 2ϩ FIGURE 1. Schematic of ESEEM data treatment+ Illustration of the isolatio...…”
Section: Mononucleotide Test Cases: Mngmp and Mnatpmentioning
confidence: 99%